Moldova Public Expenditure Review : Reforming Local Public Finance for More Efficient, Equitable, and Fiscally Sustainable Subnational Spending - World Bank (Washington, DC, 2014)
This report reviews intergovernmental fiscal relations in Moldova and recommends ways to improve the efficiency and equity of local public finance, while maintaining fiscal sustainability. Local public authorities are responsible for meeting key public service delivery needs. They play a major role in education and bear primary responsibility for urban and rural functions such as water supply and local road construction and maintenance. But local authorities are unable to fulfill this role due to sub-optimal size, inadequate financial capacity, and low administrative capacity. The Government of Moldova is reforming intergovernmental fiscal relations, as part of broader commitments under the national decentralization strategy (2012). They set new rates for sharing national taxes with the two tiers of local government, introduce formulas for transfers to local governments, and remove subordination in financial relations between top and bottom tiers of local government. This report reviews recent reforms in local public finance and makes suggestions to further improve subnational expenditures, fiscal policy, and budgetary processes. Suggestions are made in five key areas: (i) address the inefficiencies of expenditures related to the high fragmentation of Moldova's administrative-territorial organization; (ii) improve the efficiency and equity of intergovernmental transfer formulas; (iii) help develop the revenue capacity of local governments; (iv) improve public investment management at the local level; and (v) ensure sustainability of subnational debt.